Solve the equations by the use of the operator D
D²y -6Dy +9y= e^3x + e^-3x
The homogeneous equation
"(D-3)^2y=0"
The general solution of the homogeneous equation is
"y_h=(A+Bx)e^{3x}"Find the particular equation.
"L(D)=(D^2-6D+9)=(D-3)^2" has"3" as a double root. The
"L(D)y=e^{-3x}"
"y_2=\\dfrac{e^{-3x}}{L(-3)}=\\dfrac{e^{-3x}}{(-3-3)^2}=\\dfrac{e^{-3x}}{36}""y_p=y_1+y_2=\\dfrac{x^2e^{3x}}{2}+\\dfrac{e^{-3x}}{36}"
The general solution of the nonhomogeneous equation is
"y=(A+Bx)e^{3x}+\\dfrac{x^2e^{3x}}{2}+\\dfrac{e^{-3x}}{36}"
Comments
Leave a comment